2012
DOI: 10.1007/s13191-012-0158-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Occlusal Trauma on Gingival Recession and Gingival Clefts

Abstract: The aim of this study was to investigate the centric occlusal contact pattern in maximum intercuspation and to study the nature of occlusal contacts during maximum intercuspation to protrusive, lateroprotrusive and lateral excursive movements. Fifty subjects having gingival recession and ten subjects having gingival clefts belonging to age group of 18-25 years were selected after obtaining informed consent from the student's population. The selected subjects were examined and the location and extent of gingiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Current results showed that the presence and extent of mbGR were affected by the increase in the number of occlusal interferences of premolar/molar teeth in anterior or lateral guidance during mandibular movements. These findings were in line with the previous result demonstrating that occlusal interferences in maximum intercuspation and eccentric movements can contribute to the occurence of gingival lesions 9 . Again, group function occlusion demonstrated higher mbGRs in premolar/molars than in canine guided occlusion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Current results showed that the presence and extent of mbGR were affected by the increase in the number of occlusal interferences of premolar/molar teeth in anterior or lateral guidance during mandibular movements. These findings were in line with the previous result demonstrating that occlusal interferences in maximum intercuspation and eccentric movements can contribute to the occurence of gingival lesions 9 . Again, group function occlusion demonstrated higher mbGRs in premolar/molars than in canine guided occlusion.…”
Section: Discussionsupporting
confidence: 92%
“…4,5 Predisposing factors, such as occlusal interferences and malocclusions, have been associated with recession and widely investigated. [6][7][8][9][10] Malocclusions have been classified to identify the disturbances of the occlusion, planning and decision of the treatment protocols. 11,12 Currently, among the worldwide dental health-related topics malocclusions rank third, following dental caries and periodontal diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For cases with canine protection in lateral guidance, gingival recessions were observed on the buccal surfaces, while, for group protection, gingival recessions were distributed on the lingual surfaces of the anterior teeth. The authors also emphasized how occlusal interferences, in the case of dynamic occlusion associated with an absence of mutually protected occlusion, may contribute to gingival lesions, such as gingival recessions and fissures [18].…”
Section: Discussionmentioning
confidence: 99%
“…Occlusal wear was present on all teeth with gingival clefts and on almost all teeth with gingival recession. These results suggest that occlusal interferences in maximal intercuspation and eccentric movements and the absence of mutually protected occlusion can contribute to gingival recessions and clefts . It should be mentioned that in many of the aforementioned studies the oral hygiene habits of the patient, as well as other possible influencing factors, presently recognized, have not been considered.…”
Section: Role Of Trauma From Occlusion In Periodontal Diseasesmentioning
confidence: 98%